The differential presence of human polyomaviruses, JCPyV and BKPyV, in prostate cancer and benign prostate hypertrophy tissues - Shen, Chenghuang; Tung, Chunliang; Chao, Chunnun; Jou, Yeongchin; Huang, Shupei; Meng, Menghsiao; Chang, Deching; Chen, Peilain (BMC cancer, 2021)
Studies have shown that human polyomavirus infection may be associated with various human cancers. We investigated the potential relationship between the prevalence of JCPyVor BKPyV and prostate cancer (PC) in patients from Taiwan. Patients with PC and benign prostate hypertrophy (BPH; 76 and 30 patients, respectively) were recruited for this study. Paraffin-embedded tissues and clinical information of the patients were obtained. The tissue sections were used for viral DNA detection and immunohistochemistry analysis was performed for examining viral large T (LT) and VP1 proteins. Regression analysis was used to evaluate the relationship between the clinical characteristics of the patients and the risk of JCPyV/BKPyV infection. The prevalence of JCPyV/BKPyV DNA was different in PC and BPH tissues (27/76 [35.52%] and 2/30 [6.7%], respectively, p = 0.003)]. The LT and VP1 proteins were detected in 27 (35.52%) and 29 PC (38.2%) specimens, respectively, but neither protein was detected in BPH samples (p < 0.001). PC cells were more susceptible to JCPyV infection than BPH tissues [odds ratio (OR) 7.71, 95% CI: 1.71-34.09, p = 0.003). Patients with PC showing high levels of prostate-specific antigen and high Gleason scores were associated with a high risk of viral infection (ORs 1.1, 95% CI 1.000-1.003; p = 0.045 and ORs 6.18, 95% CI 1.26-30.33, p = 0.025, respectively). The expression of LT protein associated with the risk of PC increased 2923.39-fold (95% CI 51.19-166,963.62, p < 0.001). The findings indicate that JCPyV infection in PC cells may be associated with prostate cancer progression and prognosis.